FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI SULAWESI UTARA - Jusak ., Salayang; Olly Esry Harryani Laoh; Gene H. M. Kapantow (Sam Ratulangi University, 2018)
This study aims to analyze the factors that influence poverty levels in North Sulawesi. This research was conducted for three months from February to April 2018. The data used were secondary data obtained from the Central Bureau of Statistics, North Sulawesi Province and also from local bookstores, the internet through Google Scholar, to access scientific journal articles and thesis from other universities related to factors that influence poverty levels. Data collected in this study using data from January 2005 to December 2016 and presented in table form are then described and analyzed using multiple linear regression analysis. The results of the study show that the unemployment variable is a factor that significantly influences the level of poverty in North Sulawesi Province. While the level of education, the growth of Gross Regional Domestic Product (GRDP) and inflation did not significantly influence the level of poverty.*ghmk+eprm*